La constitucionalización de la formación política y su vinculación con el derecho a la educación - Ríos Rengifo, Alex Junior (Universidad ESAN, 2024)
Political education is closely related to the right to education, a fundamental right recognized internationally, which must be understood from a broad perspective to avoid any type of limitation or discrimination. Therefore, it is essential to promote its dissemination in academic and legal fields. The constant transformations that our society has undergone have encouraged the analysis of educational evolution and the inclusion of new knowledge, such as politics, in educational centers. However, prejudices persist regarding its teaching, which makes its express recognition in the legal system difficult, despite the universal approach to education. For this reason, the main objective of this study is to establish legal foundations that support its recognition in the Constitution and highlight its connection with the right to education.

La formación política guarda una relación estrecha con el derecho a la educación, un derecho fundamental reconocido internacionalmente, que debe entenderse desde una perspectiva amplia para evitar cualquier tipo de limitación o discriminación. Por ello, resulta fundamental promover su difusión en los ámbitos académico y jurídico. Las constantes transformaciones que ha sufrido nuestra sociedad han impulsado el análisis de la evolución educativa y la inclusión de nuevos conocimientos, como la política, en los centros educativos. No obstante, persisten prejuicios en torno a su enseñanza, lo que dificulta su reconocimiento expreso en el ordenamiento jurídico, a pesar del enfoque universal de la educación. Por esa razón, el objetivo principal de este estudio es establecer fundamentos jurídicos que respalden su reconocimiento en la Constitución y resaltar su conexión con el derecho a la educación.
Keywords: Political formation; Education; Fundamental right; Formación política; Educación; Constitution; Derecho fundamental; Constitución; University; Universidad; https://purl.org/pe-repo/ocde/ford#5.05.01